A COMPARATIVE ACCOUNT OF THE INTERNAL REPRODUCTIVE ORGANS IN FAMILY CHRYSOMELIDAE (COL) III, SUBFAMILES CLYTRINAE, CRYPTOCEPHALINAE AND CRIOCERINAE. - PAUNI, H. R.; DEVI, NIRMAL; TEWARI, P. KAMAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Male and female reproductive organs of 34 chrysomelid species belonging to subfamilies Clytrinae, Cryptocephalinae and Criocerinae have been described and their taxonomic significance at different levels have been discussed.